Analisis Faktor-Faktor yang Memengaruhi Kesulitan Belajar Ilmu Pengetahuan Alam pada Siswa - Noviza Rizkia; Dwi Febriani (Medan Resource Center, 2026)
Learning difficulties remain a major challenge that hinders students' academic achievement, particularly in science education, where conceptual understanding requires higher-order cognitive skills. This study aimed to identify the internal and external factors contributing to students' learning difficulties in science across different educational levels. The study employed a literature review approach by systematically examining relevant scholarly publications addressing learning difficulties among elementary, junior high, and senior high school students. The findings indicate that science learning difficulties arise from the interaction of multiple factors rather than a single cause. Internal factors include low learning motivation, limited interest in learning, and difficulties in understanding scientific concepts, such as atomic structure and compound nomenclature. External factors comprise less varied instructional methods, inadequate learning facilities, and insufficient support from families and schools. The study concludes that overcoming science learning difficulties requires comprehensive and adaptive educational strategies that integrate pedagogical innovation, supportive learning environments, and active stakeholder involvement to improve students' conceptual understanding and overall learning outcomes across educational levels.